The emerging contribution of TÜrkiye to Antarctic science and policy - Karatekin, Feride; Uzun, F. Rumeysa; Ager, Beverley J.; Convey, Peter; Hughes, Kevin Andrew (Cambridge University Press, 2023)
Antarctica is a continent dedicated to 'peace and science' and subject to international consensus-based governance through the Antarctic Treaty System. Through the Treaty, decision-making powers are reserved to Consultative Parties, which are those countries recognized as demonstrating 'substantial scientific research activity' in Antarctica. TÜrkiye acceded to the Antarctic Treaty in 1996. In its National Polar Science Program (2018-2022) it first declared a desire to attain consultative status to the Treaty. Here, we examine TÜrkiye's recent development across Antarctic science, policy and logistics. Since 2016, TÜrkiye's national Antarctic scientific output has increased threefold, ranking seventh amongst the current 27 non-Consultative Parties, and this output is greater than some Consultative Parties. TÜrkiye has submitted more papers to the Antarctic Treaty Consultative Meetings than any other non-Consultative Party and is actively participating in the development of the Antarctic Protected Area system. To facilitate longer-term research goals, TÜrkiye is constructing an Antarctic research station (Horseshoe Island, Antarctic Peninsula), has joined several polar organizations, including the Scientific Committee on Antarctic Research (SCAR) and the Council of Managers of National Antarctic Programs (COMNAP), and has developed scientific and logistical collaborations with many established Antarctic nations. The exceptionally rapid growth of TÜrkiye's Antarctic activities provides a firm foundation for the development of a future application for consultative status. © 2024 Elsevier B.V., All rights reserved.
Keywords: Antarctic logistics; Antarctic Treaty System; APECS; Committee for Environmental Protection; education and outreach; polar research